On-the-Fly Computing - Das Entwicklungs- und Betriebsparadigma für Softwaresysteme der Zukunft - Engels, Gregor (Software Engineering 2013)

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))

High-Quality Specification of Self-Adaptive Software Systems - Luckey, Markus; Engels, Gregor (Proceeding of the 8th international symposium on Software engineering for adaptive and self-managing systems)

Decision Support via Automated Metric Comparison for the Palladio-based Performance Blame Analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 4th ACM/SPEC International Conference on Performance Engineering (ICPE 2013), Prague (Czech Republic))

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen (Ninth International ACM Sigsoft Conference on the Quality of Software Architectures)

Integrating Coverage Analysis into Test-driven Development of Model Transformations - Küster, Jochen; Kovács, Dániel; Bauer, Eduard; Gerth, Christian

Automated Service Discovery and Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor

Sicherheitsherausforderungen in hochverteilten Systemen - de Meer, Hermann; Diener, Michael; Herkenhöner, Ralph; Kucera, Markus; Niedermeier, Michael; Reisser, Andreas; Schryen, Guido; Vetter, Michael; Waas, Thomas; Yasasin, Emrah (PIK - Praxis der Informationsverarbeitung und Kommunikation)

High Tech and High Touch: A Framework for Understanding User Attitudes and Behaviors Related to Smart Interactive Services. - Wünderlich, Nancy; Wangenheim, Florian V; Bitner, Mary Jo (Journal of Service Research)
Smart interactive services, in contrast with other technology-based services, require significant human-to-human interaction and collaboration in addition to the service provided by the embedded technology itself. The authors’ foundational Delphi study confirms smart interactive services (e.g., remote diagnosis, remote repair of equipment, and telemedicine) are a rapidly growing innovation category across industries. Yet, gaining user acceptance of these types of services presents a significant challenge for managers. To address this challenge, the authors employ a grounded theory approach, drawing on depth interviews, to develop a framework of barriers and facilitators to users’ attitudinal and behavioral responses to smart interactive services. The findings reveal a new set of beliefs that are critical in this context. These beliefs are tied to the human element and specifically pertain to beliefs about the “service counterpart (SC),” who is the provider’s employee controlling the technology. Control, trustworthiness, and collaboration beliefs emerge jointly as important and interrelated influencers tied to the SC. Contrary to conventional wisdom that focuses on features of the technology itself to gain user acceptance, this research encourages providers to emphasize the interpersonal elements of the service by providing control cues, raising social presence, and enhancing human trust mechanisms.
Keywords: service technology; technology-mediated service; service counterpart; smart service; remote service; technology adoption

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

Releasing multimodal data as Linguistic Linked Open Data: An experience report - Menke, Peter; McCrae, John; Cimiano, Philipp (Proceedings of the 2nd Workshop on Linked Data in Linguistics (LDL-2013): Representing and linking lexicons, terminologies and other language data)

Editorial: Internationales Personalmanagement: Den kulturellen Kontext gestalten - Kabst, Rüdiger; Wehner, M C (PERSONALquartely)

Unterstützung von Kommunalverwaltung bei Bürgerbeteiligung - Weber, P; Kabst, Rüdiger (Verwaltungskommunikation - Wissenschaftliche Analyse und praktische Beispiele)

Effektiver Einsatz von Rettungskräften bei Naturkatastrophen - Modelle und Verfahren zur Entscheidungsunterstützung - Wex, Felix; Schryen, Guido (Blick in die Wissenschaft)

Institutional Determinants of Work-Family Practices: An International Comparative Examination. - Weber, H; Wehner, M; Kabst, Rüdiger

HR-Praktiken und Innovation: Wie können Wissens- und Technologievorsprünge im Unternehmen generiert werden? - Golubovic, S; Wehner, M; Baum, M; Kabst, Rüdiger

Institutional Pressures and Interorganizational Imitation: A Quasilongitudinal Analyses of Temporary Work in the UK and Germany - Isidor, R; Wehner, M; Li, C; Kabst, Rüdiger

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)

Kompetenzorientierte Lehrerbildung - Zur Gestaltung des Praxissemesters in wirtschaftspädagogischen Studiengängen - Kremer, H.-Hugo (Standardization, professionalizationn and the measurements)

Social Media: Potenziale und Herausforderungen für die berufliche Bildung - Kremer, H.-Hugo (Standardization, professionalization and the measurements)

Forschung in Innovationsarenen: Individuelle Förderung als Herausforderung in der Bildungsarbeit in der Ausbildungsvorbereitung an Berufskollegs - Kremer, H.-Hugo; Zoyke, A. (Facetten berufs- und wirtschaftspädagogischer Forschung. Grundlagen - Herausfoderungen - Perspektiven)

Exploring Personalized Learning in the Context of the Transition System, vol. 2. Opladen - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A. (Transitions in Vocational Education, Research in Vocational Education)

Berufsbildung im Übergang - Kompetenzentwicklung in der Ausbildungsvorbereitung - Kremer, H.-Hugo (Kompetenzentwicklung in unterschiedlichen Lernkulturen)

Social Media: Potentials and Challenges for Vocational Education - Kremer, H.-Hugo (From Diagnostics to Learning Success. Proceedings in Vocational Education and Training)

Herausforderungen der Kompetenzorientierung in der Studienprogrammentwicklung - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Kompetenzorientierung ist ein wichtiges aktuelles Ziel bei der Studienprogrammentwicklung. Allerdings ist die Umsetzung in der Praxis mit zwei wesentlichen Herausforderungen verbunden: So ist zum einen der Wechsel von disziplinären Inhalten hin zu Kompetenzen wenig intuitiv; zum anderen wird die Formulierung so genannter Learning Outcomes als administrative Übung betrachtet. An der Universität St. Gallen wurde ein systematischer Prozess für die Qualitätsentwicklung der Studienprogramme eingeführt. Im Beitrag wird dieser Prozess im Hinblick auf die Kompetenzorientierung reflektiert. Es erscheint wesentlich, den Programmen möglichst viel Freiraum auf ihrem Weg zur Kompetenzorientierung zu überlassen und sie auf diese Weise zu unterstützen.
Keywords: Kompetenzorientierung; Studienprogrammentwicklung; Hochschulentwicklung; Hochschule; Learning Outcomes

Ein e-Portfolio-Konzept zur Integration heterogener Lernvoraussetzungen und Studienerfahrungen in der Lehrerbildung - Jenert, Tobias; Brahm, Taiga (Journal für LehrerInnenbildung)
Die Auseinandersetzung mit Bildungstechnologien erfolgt häufig ausgehend von einem technologischen Trend bzw. einer Klasse innovativer Werkzeuge (bspw. mobile Technologien). Es geht dann darum, die Potenziale dieser Tools für das Lernen zu ergründen, also letztlich eine Passung zwischen den technologischen Möglichkeiten und pädagogisch-didaktischen Erfordernissen zu konstruieren. In diesem Beitrag kehren wir diese Perspektive um: Ausgehend von einer bestimmten pädagogischen Problemstellung - der Bearbeitung heterogener Lernvoraussetzungen und Studienerfahrungen in der Lehrerbildung - entwickeln wir unterschiedliche didaktische Handlungsoptionen. Am Ende entsteht ein Werkzeug, das sich in Design und Funktionsumfang auf den Kern der pädagogischen Zielsetzung beschränkt.
Keywords: Portfolio; Lehrerbildung; Wirtschaftspädagogik

How Business Students Attitudes towards their University and Studying Develop during the First Year: A Qualitative Longitudinal Study - Jenert, Tobias; Brahm, Taiga
The aim of this qualitative study is first to investigate the attitude development of students in their initial year at university. College effectiveness research has shown that attitudes towards studying as well as to one's university are key factors influencing student engagement. Up to now, little is known about the processes through which such attitudes develop. Based on the theory of planned behaviour (Ajzen & Fishbein, 1980), the study addresses this research gap in three parts: a) development paths of students' attitudes towards studying and the university; b) the normative behaviour of the fellow students as well as significant persons, c) university-related experiences during the first year influencing students' attitude development. To answer these research questions, a series of five interviews was conducted throughout the first year with a total of 13 first-year students at the University of St. Gallen/Switzerland. Data analysis was performed referring to the procedures suggested by Neale (2012) for qualitative longitudinal data. To master the challenge of displaying developments over time, graphical analysis was used to construct a case history (cf. Henderson, Holland et al., 2012) for each individual. Regarding the students' developments over time, the analysis shows the participants' attitudes towards the university became more differentiated over time. A second major result concerns frictions between students' own attitudes and what they perceive to be the dominant normative behaviour. It became obvious that this developmental process is influenced by concrete incidents students experience during the first year and thus, can be shaped by structural changes.
Keywords: student attitudes; qualitative research; longitudinal study; student motivation

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

A latent growth curve analysis of Business students' intrinsic and extrinsic motivation - Brahm, Taiga; Jenert, Tobias
The proposed paper aims to investigate the longitudinal development of students' motivation over the first year of their studies at a business school by using latent growth curve modeling. The study tackles the following core research questions: How do first-year university students' intrinsic and extrinsic vary over time? Which (motivational) factors are related to students' motivational development? Although motivational dispositions have been analyzed extensively in previous studies, their longitudinal development has hitherto not been examined in the higher education context. This longitudinal study is conducted at the University of St. Gallen in Switzerland. The current sample includes 280 first-year students who have been surveyed three times and who are representative of the first-year student population. Descriptive results show that prior to their studies, students were motivated most by intrinsic factors, however, extrinsic motivation was also quite high. Employing latent growth curve modeling, it could be shown that both intrinsic and extrinsic motivation decline significantly over the course of the first year (8 months). The study contributes to motivation theory by providing further insights into the development of academic motivation over time. Latent growth curve modeling as a method can be well used for longitudinal data analysis, thus, excluding measurement error from longitudinal data. Furthermore, the study supports educational developers by determining factors influencing students' motivational development.
Keywords: motivation; intrinsic motivation; extrinsic motivation; latent growth curve modeling; longitudinal data analysis; ASEQ; higher education; studying

Die Entwicklung studien-und hochschulbezogener Einstellungen an einer Wirtschaftsuniversität: eine qualitative Längsschnittstudie - Jenert, Tobias; Brahm, Taiga
Die vorliegende Untersuchung an der Universität St. Gallen soll Erkenntnisse über die Verläufe der Einstellungsveränderungen der Studierenden geben (vgl. Brahm & Jenert, 2012). Basierend auf der Theorie des geplanten Verhaltens (Ajzen & Fishbein, 1980) werden drei Forschungsfragen adressiert: (1) Gibt es typische Pfade der Einstellungsentwicklung? (2) Wie wird das normative Verhalten von Mitstudierenden und anderen Personen wahrgenommen? (3) Welche Erfahrungen beeinflussen die Entwicklung? Zur Beantwortung dieser Fragen wurde über das erste Studienjahr hinweg eine Interviewserie mit 13 Studierenden durchgeführt. Die Datenanalyse mithilfe grafischer Case Histories zeigt, dass die Einstellungen der Probanden über die Zeit differenzierter werden. Zudem gibt es Widersprüche zwischen den Einstellungen und dem wahrgenommenen normativen Verhalten. Dabei ist die Einstellungsentwicklung von konkreten Ereignissen geprägt und kann damit durch strukturelle Interventionen beeinflusst werden.
Keywords: student attitudes; theory of planned behaviour; Einstellungsentwicklung; student motivation

Eine strategische Perspektive auf die Qualitätsentwicklung in Studienumgebungen - Jenert, Tobias; Brahm , Taiga (Lehrforschung wird Praxis: Hochschuldidaktische Forschungsergebnisse und ihre Integration in die Praxis)

Die Erforschung von Lernkulturen an Hochschulen unter Nutzung komplementärer Zugänge: Erste Erfahrungen aus einem Forschungsprogramm - Jenert, Tobias; Gebhardt , Anja (Kompetenzentwicklung in unterschiedlichen Lernkulturen, Festschrift für Dieter Euler zum 60. Geburtstag)

A Tree-form Constant Market Share Model for Growth Causes in International Trade Based on Multi-level Classification - Feng, Yuanhua; Guo, Zhichao; Peitz, Christian (Journal of Industry, Competition and Trade)

Modeling of the impact of the financial crisis and China's accession to WTO on China's exports to Germany - Guo, Zhichao; Feng, Yuanhua (Economic Modelling)

Long-Memory Processes - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita; Kulik, Rafal

A Semi-APARCH approach for comparing long-term and short-term risk in Chinese financial market and in mature financial markets - Feng, Yuanhua; Sun, Lixin

Double-conditional smoothing of high-frequency volatility surface in a spatial multiplicative component GARCH with random effects - Feng, Yuanhua

Zero Overhead Runtime Monitoring - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the 11th International Conference on Software Engineering and Formal Methods (SEFM))
Runtime monitoring aims at ensuring program safety by monitoring the program's behaviour during execution and taking appropriate action before a program violates some property.Runtime monitoring is in particular important when an exhaustive formal verification fails. While the approach allows for a safe execution of programs, it may impose a significant runtime overhead.In this paper, we propose a novel technique combining verification and monitoring which incurs no overhead during runtime at all. The technique proceeds by using the inconclusive result of a verification run as the basis for transforming the program into one where all potential points of failure are replaced by HALT statements. The new program is safe by construction, behaviourally equivalent to the original program (except for unsafe behaviour),and has the same performance characteristics.

Reflection, abstraction and theorizing in design and development research - Gregor, Shirley; Müller, Oliver; Seidel, Stefan (European Conference on Information Systems)
Keywords: Abstraction; Affordances; Design Science Research; Design Theory; Information Systems Development; Reflection; Theorizing

Designing interaction routines in service networks: A modularity and social construction-based approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (Scandinavian Journal of Information Systems)
Keywords: Business process management; Conceptual modeling; Interaction routines; Modular design; Service networks; Social construction

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Bridging the gap between manufacturing and service through IT-based boundary objects - Becker, Jorg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (IEEE Transactions on Engineering Management)
Keywords: Action research; boundary spanning; business process management (BPM); service blueprinting; service networks

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Vergleichsstudie zur Ausdrucksstärke von SMT-Solvern - Engelbrecht, Marco

Unlinkable content playbacks in a multiparty DRM system - Petrlic, Ronald; Sekula, Stephan (Data and Applications Security and Privacy XXVII)
We present a solution to the problem of privacy invasion in a multiparty digital rights management scheme. (Roaming) users buy content licenses from a content provider and execute it at any nearby content distributor. Our approach, which does not need any trusted third party - in contrast to most related work on privacy-preserving DRM - is based on a re-encryption scheme that runs on any mobile Android device. Only a minor security-critical part needs to be performed on the device's smartcard which could, for instance, be a SIM card.

Two-Stage Allocation Procedures - Röhl, Nils
Suppose some individuals are allowed to engage in different groups at the same time and they generate a certain welfare by cooperation. Finding appropriate ways for distributing this welfare is a non-trivial issue. The purpose of this work is to analyze two-stage allocation procedures where first each group receives a share of the welfare which is then, subsequently, distributed among the corresponding members. To study these procedures in a structured way, cooperative games and network games are combined in a general framework by using mathematical hypergraphs. Moreover, several convincing requirements on allocation procedures are discussed and formalized. Thereby it will be shown, for example, that the Position Value and iteratively applying the Myerson Value can be characterized by similar axiomatizations.

Towards practical privacy-preserving Digital Rights Management for Cloud Computing - Joshi, Nakul; Petrlic, Ronald (Proceedings of the 10th Annual IEEE Consumer Communications & Networking Conference (CCNC))
We propose a privacy-preserving digital rights management scheme for (future) cloud computing. Users buy software from software providers and execute it at computing centers. Our solution allows software providers to provide different license models, like execute at most n-times models. Users’ anonymity and unlinkability of actions are preserved and thus, profile building is not even possible under (a) pseudonym. Privacy protection in the honest-but-curious model is achieved by combining ring signatures with an anonymous recipient scheme.We employ secret sharing in a unique manner that allows the software provider to expose the user’s identity if the user commits fraud, e.g. by exceeding the execution limit n.

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.